A localized outbreak of Chikungunya virus in Salvador, Bahia, Brazil - Tauro, Laura Beatriz (2019)
A localized Chikungunya virus (CHIKV; East/Central/South African genotype) outbreak (50 cases, 70% laboratory-confirmed; attack rate: 5.3 confirmed cases/100 people) occurred in a Salvador, Brazil neighborhood, between Apr-Jun/2017. Highly clustered cases in space and time, mostly along a single street, highlight an increased risk of CHIKV transmission among pockets of susceptible populations. This finding underscores the need for ongoing local level surveillance for arboviral outbreaks.